Measurement of adsorption isotherms for storage and cooling applications - Kalra, Deepanshu (2014)
According to some international organisations, some of our world’s resources might run out within our lifetime. Dwindling natural resources, together with negative environmental impact have become the world’s primary concern. Hence, there is constant demand and search for new sustainable resources to ensure that enough resources are retained for our future generations’ usage. With the increased demand for environmentally friendly and energy efficient technology, many scientists are researching on adsorption and its practical applications.